2013
DOI: 10.1590/s1516-05722013000100006
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética de populações naturais de pariparoba [Pothomorphe umbellata (L.) Miq.] por RAPD

Abstract: * jsvalle@unipar.br RESUMO:O objetivo desse trabalho foi analisar a estrutura genética de populações de Pothomorphe umbellata (L.) Miq. com base em polimorfismos moleculares do tipo RAPD. Foram analisadas quatro populações naturais do estado de São Paulo (Jacareí, Jundiaí, Piquete e Ubatuba) e uma população do Paraná (Adrianópolis). Foram identificados 25 locos polimórficos (96,15%). Elevados índices de diversidade genética foram observados dentro das populações (Hs = 0,2220). Verificou-se que 65,33% da variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Owing to the importance of many medicinal plant species for popular use, or even for use in the pharmaceutical industry, many studies on the genetic diversity of native populations have been carried out. In studies with S. reticulata and P. umbellata, high genetic diversity was observed within native populations (Valle et al, 2013;Lima et al, 2015). Bandeira et al (2010) observed low genetic diversity between native populations of Jaborandi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the importance of many medicinal plant species for popular use, or even for use in the pharmaceutical industry, many studies on the genetic diversity of native populations have been carried out. In studies with S. reticulata and P. umbellata, high genetic diversity was observed within native populations (Valle et al, 2013;Lima et al, 2015). Bandeira et al (2010) observed low genetic diversity between native populations of Jaborandi.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on genetic variability and its organization in plant species, represent important steps for the exploitation, definition of genetic conservation strategies, and breeding programs (Setotaw et al, 2010). Owing to the importance of several medicinal species, either for popular use or for the pharmaceutical industry, several studies on genetic diversity in native populations have been carried out, such as those on Senna reticulata (Lima et al, 2015), Pilocarpus pennatifolius (Bandeira et al, 2010), Pothomorphe umbellata (Valle et al, 2013), and Annona crassiflora (Telles et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In Erythrina velutina, 106 bands were detected . Analysis of Pothomorphe umbellata was based on only 25 bands (Valle et al, 2013). Although no data from sufficiency analyses were available, those studies revealed high rates if polymorphism, at 87.9, 85.7, and 96.1%, respectively.…”
Section: Determining An Adequate Number Of Rapd Markers For Genetic Amentioning
confidence: 99%